Dynamics of special working capacity of skilled athlete's karate under the influence of anaerobic loads - Anatoliy Rovnyy; Volodymir Galimskyi; Natalya Boychenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: experimental verification of hypothetical models of planning a large volume glycolytic loads of targeted development of special endurance karate. Material and Methods: the experiment was attended by 25 athletes aged 16-18 years, who were divided into 5 groups (5 athletes each). We determined the rates of overall disability (IGST) and special endurance (CSR). Results: analyzed the effectiveness of the training program a combination of aerobic and anaerobic exercise. Conclusions: established the optimum combination of loads, which contributed to the development of special anaerobic endurance.